Hubungan Pengetahuan dan Sikap Terhadap Praktik Hygiene Penjamah Makanan pada Rumah Makan di Wilayah Kerja Puskesmas Wonorejo - Aprilia Ayu As Sajdah; Deny Kurniawan; Reni Suhelmi (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2022)
A food handler or food handler is a force that tends to make contact with food and also its equipment. Food handlers also participate in the expansion, cleaning, processing, transportation, and serving of food. The quality of hygiene can change depending on two factors, namely food handler factors and also the environment then from the two factors mentioned food handler factors are considered more influential. Food handlers are required to apply hygiene practices to the environment where they work and to themselves so that there is no bacterial contamination of food during the processing and serving of food so as to make the food a source of disease. Knowing whether there is a relationship between the level of knowledge and attitudes towards hygiene practices in food handlers at restaurants in the work area of the Wonorejo Health Center. In this study, it used a cross-sectional approach with purposive sampling techniques with a total sample of 61 food handlers. Data analysis used the chi square test technique which showed that there was a relationship between the level of knowledge and hygiene practices and the relationship between attitudes and hygiene with a p value = 0.000 < α 0.05. That the level of knowledge and attitude can be related to the hygiene practices of food handlers in processing and serving food. Keywords : Knowledge, Attitude, Hygiene Practices, and Food Handler